Method for manufacturing a watch bezel having luminous performance and a watch bezel manufactured thereby

KR1020260139259APending Publication Date: 2026-09-22ECCO WATCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250032091
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2026-09-22

Smart Images

  • Figure PAT00001_ABST
    Figure PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a watch bezel having phosphorescent performance, comprising the steps of: (a) mixing 100 parts by weight of zirconia powder and 1 to 35 parts by weight of strontium aluminate-based phosphorescent powder to obtain a mixture; (b) molding the mixture of step (a) to obtain a molded article; and (c) firing the molded article of step (b) to obtain a fired article.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a watch bezel having phosphorescent performance and a watch bezel manufactured according to the same. Background Technology

[0002] A bezel refers to the rim that secures the glass to the watch face, and numbers or markings are displayed on the bezel to indicate minutes.

[0003] While metal has traditionally been the dominant material for bezels, ceramic materials are also being widely used recently. In particular, zirconium bezels are used in high-end wristwatches, and there is a demand for the development of new ceramic materials with differentiated colors and functional characteristics to survive in a fiercely competitive market. Prior art literature

[0004] Republic of Korea Registered Patent No. 10-2454163 (Published on Oct. 12, 2022) The problem to be solved

[0005] The problem that the present invention aims to solve is to provide a method for manufacturing a watch bezel that has excellent mechanical properties and chemical stability, as well as excellent phosphorescent performance. means of solving the problem

[0006] The present invention provides, in one embodiment, a method for manufacturing a watch bezel having phosphorescent performance, comprising: (a) mixing 100 parts by weight of zirconia powder and 1 to 35 parts by weight of strontium aluminate-based phosphorescent powder to obtain a mixture; (b) molding the mixture of step (a) to obtain a molded article; and (c) firing the molded article of step (b) to obtain a fired article.

[0007] In addition, step (a) may further mix 0 to 25 parts by weight of additives based on 100 parts by weight of zirconia powder.

[0008] In addition, the zirconia powder in step (a) is zirconia oxide (ZrO2) powder or 3 mol% yttira (Y2O3) It may be stabilized zirconia, specifically, 3 mol% yttira (Y2O3) It can be stabilized zirconia.

[0009] In addition, step (b) can be performed by mixing the mixture of step (a) and the injection binder in a volume ratio of 1:0.5 to 2, kneading the mixture, and then injecting it into a watch bezel mold and injection molding.

[0010] In addition, step (b) can be pressure molded by mixing 0 to 10 parts by weight of a pressure binder into the mixture of step (a).

[0011] In addition, in step (b), pressure molding can be performed under pressure conditions of 400 to 2,500 kg / ㎠.

[0012] In addition, the injection binder may be a polyolefin-based binder.

[0013] In addition, polyolefin-based binders may include polyethylene, paraffin wax, stearic acid, and plasticizers.

[0014] In addition, the pressurized binder may be a polyvinyl alcohol-based binder.

[0015] In addition, the polyvinyl alcohol-based binder may include polyvinyl alcohol, a plasticizer, and a lubricant.

[0016] In addition, step (c) can be performed at a temperature of 1,150 to 1,700 ℃ for 1 to 12 hours.

[0017] In addition, the additive may be one or more selected from the group consisting of strontium, aluminum, alkali metal, lanthanide metal, alkali metal oxide, lanthanide metal oxide, alkali metal oxide salt, lanthanide metal oxide salt, nitrate, carbonate, hydroxide salt, fluoride salt, iodide salt, bromide salt, chloride salt, chloride salt, phosphate, borate, sulfonate, sulfate, stearate, acetylacetonate, myristate, and acetate.

[0018] In another embodiment, the present invention provides a watch bezel having phosphorescent performance manufactured by the method described above.

[0019] In addition, the bezel may have an average Vickers hardness value (Hv) of 500 to 1,300.

[0020] In addition, the bezel can have a bending strength value of 200 to 1,200 MPa. Effects of the invention

[0021] According to the present invention, a watch bezel with excellent mechanical properties and chemical stability, as well as excellent phosphorescent performance, can be provided. Brief explanation of the drawing

[0022] Figure 1 is a flowchart illustrating a method for manufacturing a watch bezel having phosphorescent performance. Figure 2 shows the results of measuring Vickers hardness values ​​according to the content of phosphorescent powder. Figure 3 shows the results of measuring the bending strength according to the content of phosphorescent powder. Figure 4 shows the results of analyzing afterglow luminance according to the content of phosphorescent powder (comparing afterglow retention characteristics in a dark room after exposure to a triphosphor fluorescent lamp for 10 minutes). Figure 5 is the result of verifying the phosphorescent performance of a watch bezel having phosphorescent performance manufactured according to Example 1. Figure 6 is the result of verifying the phosphorescent performance of a watch bezel having phosphorescent performance manufactured according to Examples 2 to 7. Specific details for implementing the invention

[0023] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings so that those skilled in the art can easily implement the present invention. However, the present invention may be implemented in various different embodiments and is not limited to the embodiments described herein. Throughout the specification, similar parts are denoted by the same reference numerals.

[0025] The present invention is characterized by maintaining the basic mechanical and chemical properties of ceramics as a conventional watch case material while exhibiting phosphorescent performance above a certain level.

[0026] Figure 1 is a flowchart illustrating a method for manufacturing a watch bezel having phosphorescent performance.

[0027] Referring to FIG. 1, a method for manufacturing a watch bezel having phosphorescent performance, which is an embodiment of the present invention, will be described.

[0028] In one embodiment, the present invention provides a method for manufacturing a watch bezel having phosphorescent performance, comprising: (a) a step of obtaining a mixture by mixing 100 parts by weight of zirconia powder and 1 to 35 parts by weight of strontium aluminate-based phosphorescent powder (S100); (b) a step of obtaining a molded product by molding the mixture of step (a) (S200); and (c) a step of obtaining a sintered product by firing the molded product of step (b) (S300).

[0030] Step (a) of obtaining the mixture

[0031] First, as shown in FIG. 1, a step (S100) is performed to obtain a mixture by mixing zirconia powder and strontium aluminate-based phosphorescent powder.

[0032] In step (a), the mixture may be mixed with 1 to 35 parts by weight of strontium aluminate-based phosphorescent powder based on 100 parts by weight of zirconia powder, specifically 5 to 25 parts by weight of strontium aluminate-based phosphorescent powder, and more specifically 10 to 15 parts by weight of strontium aluminate-based phosphorescent powder.

[0033] If the content of the strontium aluminate-based phosphorescent powder is less than 1 part by weight, the desired phosphorescent performance cannot be achieved, and if the content exceeds 35 parts by weight, the content of the zirconia powder is relatively low, which may lead to a decrease in mechanical properties.

[0034] In step (a), the zirconia powder is ZrO2, Zr2O3, and 3 mol% yttria (Y2O3) It may be one selected from the group consisting of stabilized zirconia, specifically, 3 mol% yttria(Y2O3) It can be stabilized zirconia.

[0035] Step (a) consists of mixing zirconia powder and strontium aluminate-based phosphorescent powder, ball milling, and drying.

[0036] The ball milling process can be performed by adding zirconia powder and strontium aluminate-based phosphorescent powder to ethanol in the aforementioned amounts and using a ball mill.

[0037] At this time, zirconia can be used for the ball, and the process can be performed for 12 to 36 hours, specifically 24 hours.

[0038] The drying process can be performed using a dryer at 80 to 100 ℃ conditions, specifically at 90 ℃ conditions.

[0039] Step (a) may further mix 0 to 25 parts by weight of additives based on 100 parts by weight of zirconia powder, specifically 0.01 to 25 parts by weight, more specifically 0.1 to 10 parts by weight.

[0040] By further mixing the additive in step (a), improved phosphorescent performance can be achieved through the strontium aluminate-based phosphorescent powder and the additive.

[0041] The additive may be one or more selected from the group consisting of strontium, aluminum, alkali metals, lanthanide metals, alkali metal oxides, lanthanide metal oxides, alkali metal oxide salts, lanthanide metal oxide salts, nitrates, carbonates, hydroxides, fluorides, oxalates, bromides, chlorates, chlorides, phosphates, borates, sulfonates, sulfates, stearates, acetylacetonates, myristates, and acetates; specifically, strontium, aluminum, alkali metals, lanthanide metals, alkali metal oxides, lanthanide metal oxides, alkali metal oxide salts, and lanthanide metal oxide salts. It is possible.

[0042] In addition, alkali metals may include metal ions such as lithium, sodium, potassium, cesium, rubinium, and francium, and may be metal oxides, nitrates, carbonates, hydroxides, fluorides, oxides, chlorides, iodides, bromides, sulfonates, and chlorates.

[0044] Step (b) of obtaining a molded product

[0045] Next, as illustrated in FIG. 1, a step (S200) of molding the mixture of step (a) to obtain a molded product is performed.

[0046] Specifically, step (b) may be performed by mixing the mixture of step (a) and an injection binder in a volume ratio of 1:0.5 to 2, kneading the mixture, and then injecting it into a watch bezel mold for injection molding, or by mixing 0 to 10 parts by weight of a pressure binder into the mixture of step (a) for pressure molding.

[0047] In step (b), the mixing can be performed by mixing the mixture from step (a) and the binder in a volume ratio of 1:0.5 to 2 and for 30 to 120 minutes at a temperature of 160 to 180 °C, specifically by mixing the mixture from step (a) and the binder in a volume ratio of 1:1 and for 60 minutes at a temperature of 170 °C.

[0048] If the above conditions are not met, the mixing may not be perfect, and the quality of the molded product may be degraded.

[0049] In step (b), the injection binder is a polyolefin-based binder and may include polyethylene, paraffin wax, stearic acid, and plasticizers, and any binder applicable to the technology may be used without limitation.

[0050] In step (b), injection molding can be performed under pressure conditions of 400 to 2,500 kg / ㎠, specifically under pressure conditions of 900 to 1,100 kg / ㎠, and more specifically under pressure conditions of 1,000 kg / ㎠.

[0051] The injection molding time is not limited, and it can be terminated once the molding is completed perfectly.

[0052] Pressure molding can be performed by mixing 0 to 10 parts by weight, specifically 0.01 to 10 parts by weight, of a pressure binder into the mixture of step (a).

[0053] The pressure binder is a polyvinyl alcohol-based binder and may include a plasticizer and a lubricant.

[0054] At this time, the molded product can be molded to have a thickness of about 4 to 5 mm.

[0055] After step (b), before performing step (c), a step of pyrolyzing the molded product obtained through step (b) may be further included.

[0056] The pyrolysis step is for removing the binder added for injection molding of the molded product, and the binder can be removed from the molded product by pyrolyzing it while slowly increasing the temperature to 400°C by introducing it into a degreasing machine.

[0058] Step (c) of obtaining the calcined product

[0059] Finally, as illustrated in FIG. 1, a step (S300) is performed to obtain a sintered product by firing the molded product of step (b).

[0060] The firing of step (c) is performed for the long afterglow characteristics of the watch bezel.

[0061] Step (c) can be performed for 2 to 12 hours at a temperature of 1,150 to 1,700 ℃, and specifically, for 2 to 4 hours at a temperature of 1,250 to 1,500 ℃.

[0062] If the firing temperature is below 1,150 ℃, the zirconia powder and strontium aluminate-based phosphorescent powder are not densified, resulting in reduced mechanical properties and a decrease in the quality of the final product. If the firing temperature exceeds 1,700 ℃, excessive grain growth of the zirconia powder and the formation of unwanted secondary phases or impurities in the strontium aluminate-based phosphorescent powder may occur, leading to a decrease in phosphorescent performance or a failure to exhibit it.

[0063] In addition, if the firing time is less than 1 hour, the firing is not completed perfectly and the desired physical properties cannot be achieved, and if the firing time exceeds 12 hours, excessive grain growth, phase transition, or the formation of unwanted impurity phases of the zirconia powder may occur, which may degrade the physical properties.

[0064] In order to prevent the formation of a secondary phase or impurity phase in step (c), P O2 and P H2OIt can be performed in an atmosphere that minimizes partial pressure, specifically in a vacuum atmosphere, an inert gas (He, Ar, N2), or a reducing gas (H2).

[0065] For example, to create a reducing atmosphere, it can be performed in an atmosphere containing 5% ≤ H2 ≤ 50% and 50% ≤ Ar, N2, He ≤ 95%.

[0066] In this case, if the hydrogen content is less than 5%, there is a problem in that the desired luminescence characteristics cannot be obtained.

[0067] In addition, in step (c), sintering can be carried out by isotropic pressure sintering under pressure conditions of 500 to 1,500 bar to improve density. In this case, the sintered body can achieve high density and improve mechanical properties, afterglow brightness, and long afterglow characteristics. The gas used for pressurization may be argon, nitrogen, helium, or hydrogen.

[0068] After step (c), a step of cooling the sintered product may be further included, and the method is not limited.

[0070] In another embodiment, the present invention provides a watch bezel having phosphorescent performance manufactured by the method described above.

[0071] In addition, the bezel may have an average Vickers hardness value (Hv) of 500 to 1,300.

[0072] In addition, the bezel can have a bending strength value of 200 to 1,200 MPa.

[0074] The present invention will be described in more detail below using examples. These examples are solely for the purpose of more specifically explaining the present invention, and it is obvious to those skilled in the art that the scope of the present invention is not limited by them.

[0075] <Preparation Examples 1 to 6>

[0076] Based on 100 parts by weight of zirconia powder, 5 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 50 parts by weight, and 70 parts by weight of strontium aluminate-based phosphorescent powder were mixed, and each mixture was prepared.

[0077] Subsequently, each mixed powder was placed into a square mold of 5.7 × 70 mm and pressurized with a molding pressure of 1,000 kg / ㎠ to produce a molded body with a thickness of 4.5 mm. The molded body was placed into a reducing atmosphere firing furnace and gradually heated to 1,350 ℃, maintained for 2 hours, and then naturally cooled to produce a sample having phosphorescent properties.

[0078] At this time, the reducing atmosphere was formed by introducing Ar gas and H2 gas in a 2:1 volume ratio, and the gas was used with a purity of 99.9% to minimize exposure to oxygen and moisture during firing.

[0079] Table 1 below shows the content of phosphorescent powder and the volume ratio of phosphorescent powder of samples prepared according to Preparation Examples 1 to 3.

[0080] division Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 Preparation Example 5 Preparation Example 6 phosphorescent powder content (parts by weight) 5 10 20 30 50 70 Luminous volume ratio (%) 8.5 16.39 30.61 43.06 63.83 80.46

[0082] <Test Example>

[0083] Test Example 1: Vickers Hardness Measurement

[0084] To evaluate the mechanical properties of the examples prepared according to Examples 1 to 6, the samples were ground to a size of 4 × 3 × 50, and the edges were machined to an R of 0.2 so that microcracks would not affect the strength value.

[0085] The processed sample was subjected to 3-point bending strength and Vickers hardness measurements to determine a composition range having mechanical properties at a level suitable for use as a decorative member.

[0086] Table 2 below shows the results.

[0087] division Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 Preparation Example 5 Preparation Example 6 Vickers hardness (Hv) average of 10 measurements 1026 862 770 666 Unmeasurable Unmeasurable

[0088] Referring to Table 2, when looking at the results of the Vickers hardness measurement, Preparation Examples 5 and 6, in which 50 parts by weight and 70 parts by weight of phosphorescent powder were added, were unsuitable to the extent that Vickers hardness measurement was impossible. In contrast, Preparation Examples 1 to 4, in which 30 parts by weight or less were added, all showed excellent Vickers hardness values, and Preparation Examples 1 and 2 were particularly excellent. Additionally, referring to Figure 2, it can be confirmed that a Vickers hardness value of 800 or higher, which is known to be generally required for scratch-resistant materials applicable as watch case decoration materials, is added at a level of about 17% or less.

[0090] Test Example 2: Bending Strength Measurement

[0091] The bending strength of samples prepared according to Preparation Examples 1 to 6 was measured and is shown in Table 3 below.

[0092] division Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 Preparation Example 5 Preparation Example 6 Bending strength (Mpa, 3 points) 454 329 221 143 66 40

[0093] Referring to Table 3 and Figure 3, when looking at the bending strength measurement results, it is determined that the level suitable for use as an exterior material for watch decorative members is a bending strength ≥ 300 MPa or higher, and when calculating the phosphorescent powder as about 12% by weight, about 14.15 parts by weight should be added based on 100 parts by weight of zirconia powder.

[0095] Test Example 3: Afterglow Luminance Measurement

[0096] To evaluate afterglow luminance characteristics and afterglow retention time, samples prepared according to Preparation Examples 1 to 6 were simultaneously exposed to a light source for the same amount of time and then maintained in a dark room, and the afterglow luminance according to retention time was compared.

[0097] Figure 4 shows the results.

[0098] Referring to Fig. 4, it can be seen that Preparation Example 1 was almost completely lost after 10 minutes, Preparation Example 2 was almost completely lost after 15 minutes, and Preparation Examples 3 to 6 all maintained similar afterglow characteristics until 20 minutes were maintained.

[0099] It can be confirmed that when phosphorescent powder is added in an amount exceeding a certain level, there is no significant difference in afterglow brightness and afterglow retention time. Therefore, it can be confirmed that for a material suitable for a watch decorative bezel, the phosphorescent powder content is optimal at approximately 12 weight% (14.15 weight parts).

[0100] It is confirmed that about 12 weight percent of phosphorescent powder has a volume ratio of about 8:2 with respect to zirconia powder, and through this, it can be confirmed that excellent phosphorescent performance can be achieved with a luminescent surface area of ​​about 20%.

[0102] <Example>

[0103] Example 1

[0104] A mixture of zirconia powder (3 mol% Y2O3-ZrO2) and 12.4 wt% strontium aluminate-based phosphorescent powder was mixed in a ball mill filled with ethanol and zirconia balls for 24 hours, and then the slurry was dried in a dryer heated to 90°C.

[0105] The dried mixed powder and an injection molding binder were mixed in a 1:1 volume ratio at 170°C for 1 hour. The binder used was a polyolefin-based injection binder, and the main components were polyethylene, paraffin wax, stearic acid, and a small amount of plasticizer (hexamolintitch, BASF).

[0106] Afterwards, to remove the polyolefin-based binder added for injection molding, the molded product was placed in a degreasing tank and slowly heated to 400°C to remove it by thermal decomposition.

[0107] A degreased body from which the binder had been removed was placed in a sintering furnace, and a mixture of Ar and H2 in a 2:1 ratio was added. The temperature was raised to 1350 ℃, maintained for 2 hours, and then naturally cooled to manufacture a bezel, which is a decorative component of a watch. At this time, the manufactured bezel emitted a bright light green color in the dark.

[0108] Figure 5 is an image showing a bezel having phosphorescent performance manufactured according to Example 1.

[0110] Examples 2 to 7

[0111] A mixture of zirconia powder (5.2% Y2O3-ZrO2), 12.4 wt% strontium aluminate-based phosphorescent powder, and x wt% lanthanide metal oxide was mixed for 24 hours in a ball mill filled with ethanol and zirconia balls, and then the slurry was dried in a dryer heated to 90°C.

[0112] Afterward, the dried mixed powder was ground and sieved through a 150 Mesh sieve, placed into a circular mold, and subjected to a molding pressure of approximately 1,000 kg / ㎠. It was then placed in a sintering furnace, heated to 1,350 ℃ in a mixed gas atmosphere with an Ar / H2 ratio of 2 / 1, maintained for 2 hours, and then naturally cooled to produce a bezel that has a beautiful color even under natural light and possesses afterglow brightness and long afterglow characteristics.

[0113] The types and content (x) of lanthanide metal oxides are shown in Table 4 below.

[0114] Referring to Fig. 6, it can be seen that compared to a material manufactured by adding only conventional strontium aluminate, it has superior color in natural light and long blue afterglow characteristics.

[0115] Classification (Weight%) Nd2O3 H2O3 Pr6O 11 CeO2 TbO7 Er2O3 Example 2 3.0 wt% Example 3 1.0 wt% Example 4 1.0 wt% Example 5 0.22 wt% Example 6 0.1 wt% Example 7 1.5 wt%

[0116] According to the present invention, it is possible to provide a watch bezel that not only has excellent mechanical properties and chemical stability but also excellent phosphorescent performance. The present invention, as described above with reference to the attached drawings, is capable of various modifications and changes by a person skilled in the art, and such modifications and changes should be interpreted as being included within the scope of the rights of the present invention. Explanation of the symbols

[0117] S100: Step to obtain the mixture S200: Step to obtain the molded product S300: Step to obtain calcined material

Claims

Claim 1 A method for manufacturing a watch bezel having phosphorescent performance, comprising: (a) a step of mixing 100 parts by weight of zirconia powder and 1 to 35 parts by weight of strontium aluminate-based phosphorescent powder to obtain a mixture; (b) a step of molding the mixture of step (a) to obtain a molded product; and (c) a step of firing the molded product of step (b) to obtain a fired product. Claim 2 A method for manufacturing a watch bezel having phosphorescent performance, wherein, in claim 1, step (a) further mixes 0 to 25 parts by weight of an additive based on 100 parts by weight of the zirconia powder. Claim 3 In claim 1, the zirconia powder in step (a) is zirconia oxide (ZrO2) powder or 3 mol% yttira (Y2O3) Method for manufacturing a watch bezel having phosphorescent properties, made of stabilized zirconia. Claim 4 A method for manufacturing a watch bezel having phosphorescent performance, wherein in claim 1, step (b) is to mix the mixture of step (a) and an injection binder in a volume ratio of 1:0.5 to 2, knead the mixture, then pour it into a watch bezel mold and injection mold it. Claim 5 A method for manufacturing a watch bezel having phosphorescent performance, wherein, in claim 1, step (b) involves mixing 0 to 10 parts by weight of a pressure binder into the mixture of step (a) and pressure molding. Claim 6 A method for manufacturing a watch bezel having phosphorescent performance, wherein, in claim 5, the pressure molding in step (b) is performed under pressure conditions of 400 to 2,500 kg / ㎠. Claim 7 A method for manufacturing a watch bezel having phosphorescent performance, wherein, in paragraph 4, the injection binder is a polyolefin-based binder. Claim 8 A method for manufacturing a watch bezel having phosphorescent performance, wherein the polyolefin-based binder according to claim 7 comprises polyethylene, paraffin wax, stearic acid, and a plasticizer. Claim 9 A method for manufacturing a watch bezel having phosphorescent performance, wherein, in paragraph 5, the pressure binder is a polyvinyl alcohol-based binder. Claim 10 In claim 9, the method for manufacturing a watch bezel having phosphorescent performance, wherein the polyvinyl alcohol-based binder comprises polyvinyl alcohol, a plasticizer, and a lubricant. Claim 11 A method for manufacturing a watch bezel having phosphorescent performance, wherein, in claim 1, step (c) is performed at a temperature of 1,150 to 1,700 ℃ for 1 to 12 hours. Claim 12 A method for manufacturing a watch bezel having phosphorescent performance according to claim 2, wherein the additive is one or more selected from the group consisting of strontium, aluminum, alkali metal, lanthanide metal, alkali metal oxide, lanthanide metal oxide, alkali metal oxide salt, lanthanide metal oxide salt, nitrate, carbonate, hydroxide salt, fluoride salt, iodide salt, bromide salt, chlorate, chloride salt, phosphate, borate, sulfonate, sulfate, stearate, acetylacetonate, myristate, and acetate. Claim 13 A watch bezel having phosphorescent performance manufactured by any one of the methods of paragraphs 1 to 12. Claim 14 In claim 11, the bezel is a watch bezel having phosphorescent performance, having an average Vickers hardness value (Hv) of 500 to 1,300. Claim 15 In claim 11, the above bezel is a watch bezel having phosphorescent performance with a bending strength value of 200 to 1,200 Mpa.